2015
DOI: 10.1038/nbt.3295
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing of DNA G-quadruplex structures in the human genome

Abstract: G-quadruplexes (G4s) are nucleic acid secondary structures that form within guanine-rich DNA or RNA sequences. G4 formation can affect chromatin architecture and gene regulation and has been associated with genomic instability, genetic diseases and cancer progression. Here we present a high-resolution sequencing-based method to detect G4s in the human genome. We identified 716,310 distinct G4 structures, 451,646 of which were not predicted by computational methods. These included previously uncharacterized non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
1,085
1
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,003 publications
(1,132 citation statements)
references
References 32 publications
(43 reference statements)
38
1,085
1
8
Order By: Relevance
“…It is of note that hypersensitive DNA cleavage sites have been described adjacent to G4DNA sequences in mitochondria (52,78,79) and proto-oncogenes (80,81). Recent results from the Balasubramanian laboratory support the conclusion that a very large number of DNA sequences throughout the genome can fold into quadruplex structures in addition to telomeric sequences (82). Hence, nuclear and mitochondrial human DNA has great potential for producing G4DNA during repair or excision of damaged DNA.…”
Section: Discussionmentioning
confidence: 58%
“…It is of note that hypersensitive DNA cleavage sites have been described adjacent to G4DNA sequences in mitochondria (52,78,79) and proto-oncogenes (80,81). Recent results from the Balasubramanian laboratory support the conclusion that a very large number of DNA sequences throughout the genome can fold into quadruplex structures in addition to telomeric sequences (82). Hence, nuclear and mitochondrial human DNA has great potential for producing G4DNA during repair or excision of damaged DNA.…”
Section: Discussionmentioning
confidence: 58%
“…S1D; Supplemental Tables 1, 2), possibly due to the GC-rich nature of the mouse L1 3 ′ end sequence (Chambers et al 2015). Furthermore, the de novo L1 insertions had relatively long poly(A) tracts (average ∼64 bp), reducing the likelihood that L1 3 ′ end sequence and flanking genomic DNA would be captured in a single sequencing read.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to telomeric G4s, it was shown using genome sequencing that approximately 700,000 DNA G4-like sequences, 81 while bioinformatic studies reported around 350,000 sequences with the potential to form G4 structures. 82 Finally, immunoprecipitating G4…”
Section: Promoter G4smentioning
confidence: 99%